Pembelajaran Online Berbasis Media Google Formulir dalam Tanggap Work From Home Masa Pandemi Covid-19 di Madrasah Ibtidaiyah Negeri (MIN) 1 Paser - Bulan, Sri; Zainiyati, Husniyatus Salamah (SYAMIL: Journal of Islamic Education, 2020)
Google Forms works as a form of professionalism in the midst of the COVID-19 pandemic in making students keep learning. Preparation to work from home is anticipated with socialization activities using Google Forms as a first step to the success of the education process through online learning. This research was conducted online with data sources of 41 MIN 1 Paser educational community with data collection techniques through interviews, non-participant observation, and document studies. Using a qualitative approach in the form of case studies, data are collected interactively according to the Miles and Huberman models. The results show: MIN 1 Paser teachers during work from home are using Google Forms as an education room and assignment bag during online learning activities. Teacher professionalism is built to always be creative and innovate in the Google Form space. Present meaningful teaching with learning videos and quizzes that motivate students. Create a new cultural tradition of teaching from paper to online form sheets.